Governance and Challenges in the Management of Zakat, Infaq, and Sadaqah: A Case Study of Bengkulu Provincial BAZNAS - Hendri Hendri; Taufik Romadon (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the management of zakat, infaq, and sadaqah (ZIS) at Bengkulu Provincial BAZNAS and to analyze its role as an Islamic social finance instrument in supporting regional economic growth and improving mustahik welfare. Specifically, the research evaluates ZIS management effectiveness, fundraising strategies, human resource development, and internal and external challenges in optimizing productive and sustainable utilization of ZIS. Methodology: A descriptive qualitative approach was adopted, involving in-depth interviews, direct observation, and documentation review with BAZNAS management, amil, mustahik, and internal supervisors. Data were analyzed using the Miles and Huberman interactive model, with validity ensured through source and methodological triangulation. Findings: ZIS management at Bengkulu Provincial BAZNAS adheres to Islamic principles, legal regulations, and SOPs. Digital systems, especially SIMBA, have improved transparency, accountability, and efficiency. Zakat collection is influenced by muzaki awareness, socialization efforts, and local government support. Productive ZIS programs, particularly MSME empowerment, enhance mustahik income and economic resilience, though challenges remain in human resources, digital infrastructure, zakat literacy, and direct distribution practices. Originality: This study contributes a concise model for effective and transparent ZIS management, highlighting how transforming consumptive zakat into productive programs supports sustainable regional economic development. It also strengthens understanding of the role of zakat institutions in promoting financial inclusion, poverty alleviation, and equitable welfare distribution within the Bengkulu context. Conclusions: The study concludes that ZIS management at Bengkulu Provincial BAZNAS has demonstrated significant progress through digitalization and productive program initiatives, yet continued efforts in human resource capacity building, infrastructure development, and public literacy are essential to fully realize its potential as a driver of regional economic growth and mustahik welfare. Type of Paper: This paper is an empirical research paper.